Refrigerating fluid-resistant nylon material applied to heat management system of new energy automobile

By adding additives such as epoxy silicone to the nylon material formula and performing glass fiber surface pretreatment, the problem of nylon material failure in high-temperature refrigerant environment is solved, and the high-performance refrigerant resistance of nylon material is achieved, which is suitable for components of thermal management systems of new energy vehicles.

CN119842225APending Publication Date: 2025-04-18SHANGHAI PRET COMPOSITES +3

Patent Information

Application Number
CN202411978023.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Existing nylon materials are prone to failure in high-temperature refrigerant environments, resulting in insufficient refrigerant resistance of thermal management system components and cannot meet the high-performance requirements of new energy vehicles for components.

Method used

The formulation design adds additives such as epoxy silicone, combined with the surface pretreatment of glass fiber and the use of compatibility agents, enhance the interface bonding and compatibility between nylon materials and glass fiber, and improve its refrigerant resistance.

Benefits of technology

The prepared nylon material exhibits excellent refrigerant resistance, mechanical properties and long-term thermal oxygen aging performance in high-temperature refrigerant environments, and is suitable for automotive thermal management system components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005220885380000031
    Figure BDA0005220885380000031
  • Figure BDA0005220885380000032
    Figure BDA0005220885380000032
  • Figure BDA0005220885380000071
    Figure BDA0005220885380000071
Patent Text Reader

Abstract

The invention discloses a refrigerating fluid-resistant nylon material applied to a heat management system of a new energy automobile and a preparation method of the refrigerating fluid-resistant nylon material. The refrigerating fluid-resistant nylon material is prepared from the following raw materials in percentage by weight: 37-89.98% of nylon resin; 10 to 55% of modified glass fiber; 0.01 to 5% of a compatilizer; 0.01 to 1% of an antioxidant; 0-2% of other additives; the surface of the glass fiber is subjected to sizing treatment through a solution containing epoxy siloxane, and the mass fraction of a sizing agent is larger than 0.3%. The nylon material prepared by the invention has excellent mechanical properties, long-term thermo-oxidative aging resistance and freezing liquid resistance, and can be used for parts such as PTC (Positive Temperature Coefficient) outer plates of automobile thermal management systems, thermostats, water valves and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of polymer materials, and in particular to a freezing liquid resistant nylon material used in a thermal management system of a new energy vehicle. Background Art

[0002] Fuel vehicles increase the risk of scrapping engines and gearboxes in high temperature environments, increase resistance and fuel consumption in low temperature environments, and pure electric vehicles are prone to thermal runaway in high temperature environments, and discharge performance deteriorates in low temperature environments. The automotive thermal management system plays an important role in ensuring the functional safety and service life of the vehicle. The main function of the automotive thermal management system is to ensure that different parts can work at the appropriate temperature through means such as heat dissipation, heating, and heat preservation.

[0003] The thermal management system of traditional fuel vehicles includes the cooling of the engine / mechanical box, the passenger compartment air conditioning system and the intake air thermal management. The thermal management of pure electric vehicles includes the thermal management of the three-electric system and the passenger compartment. The automotive thermal management system is assembled from upstream water pumps, condensers and other components to provide functional safety and service life guarantees for downstream vehicles. The thermal management system of pure electric vehicles has undergone major changes in coverage and implementation methods compared to the thermal management system of fuel vehicles, and its requirements for the energy saving and safety of components are relatively higher. The functionality and value increment of products such as valves, heat exchangers, pumps, pipelines, and PTC are further improved, and the material selection requirements for components are relatively more stringent. Nylon material has excellent high temperature resistance, high strength, good resistance to refrigerants and processing performance, and is the preferred material for components such as PTC outer panels, thermostats, and water valves in the thermal management system.

[0004] Chinese patent CN202323234385.1 provides a new application of dendritic polyamide-amine polymers. The dendritic polyamide-amine polymers can reduce the attack reaction ratio of water and / or alcohol on the terminal carboxyl group, thereby improving the hydrolysis and alcoholysis resistance of the polyamide composition. At the same time, the densely packed active functional groups on the surface of the dendritic polyamide-amine polymers can establish a cross-linked structure between different polyamide molecular chains, thereby improving the melt strength and uniformity, and ensuring the melt fluidity, so that the bubbles in the polyamide composition are easy to grow and difficult to break during the Mucell molding process, and a uniform and dense microporous structure is formed, thereby maintaining a high performance retention rate of the polyamide composition, and obtaining finished products with good appearance. Chinese invention patent CN202211241820.0 discloses a hydrolysis-resistant and alcoholysis-resistant reinforced nylon material and its preparation method. By compounding the raw materials and adding heat stabilizers and hydrolysis-resistant agents, a high-performance hydrolysis-resistant reinforced nylon material is obtained, so that it can be continuously immersed in 135°C ethylene glycol antifreeze for more than 120 hours, and the tensile strength remains above 70%, thereby avoiding the high temperature and humidity environment that will accelerate the hydrolysis of the nylon material, resulting in a decrease in material performance and danger. Chinese patent CN202011278992.6 discloses an alcoholysis-resistant reinforced PA6T material and its preparation method. The compatibilizer is a styrene-N-phenylmaleimide copolymer, which can capture alcohol substances that invade the inside of the material, play an active defense role, improve the bonding force between the glass and the matrix resin, and make the material have good alcoholysis resistance. Related technologies have conducted some research on the effects of dendritic polymers, hydrolysis-resistant additives and compatibilizers on the alcoholysis resistance of nylon materials. However, the research content is limited to reducing the water absorption of nylon, increasing polyamide crosslinking and improving the stability of the molecular structure to improve the cryogenic resistance of nylon materials. Cryogenic resistance failure usually occurs when the interface between nylon resin and glass fiber is destroyed in high-temperature cryogenic liquids. There is little research on the effects of the interface between resin and glass fiber and the improvement of the heat resistance of nylon materials on the cryogenic resistance of nylon materials. Summary of the invention

[0005] The purpose of the present invention is to provide a nylon material resistant to freezing liquid used in the thermal management system of new energy vehicles. The additives in the formula design make the nylon material have both heat resistance and freezing liquid resistance. At the same time, the influence of compatibilizer and glass fiber interface treatment on the freezing liquid resistance of the nylon material is studied, which is of great significance for studying nylon materials suitable for automotive thermal management system components. The nylon material prepared by this method can meet the performance requirements of thermal management system components for nylon materials.

[0006] The objective of the present invention is achieved through the following technical solutions:

[0007] A freezing liquid-resistant nylon material used in a thermal management system of a new energy vehicle comprises the following raw materials in percentage by weight: nylon resin: 37-89.98%; modified glass fiber: 10-55%; compatibilizer: 0.01-5%; antioxidant: 0.01-1%; the surface of the glass fiber is sizing treated with an epoxysilicone solution, and the mass fraction of the sizing agent is greater than 0.3%.

[0008] The modified glass fiber has an alkali content of less than 0.8% and a volume density of 0.6-0.8 g / cm 3 , single fiber diameter: 7-13μm, short cut length: 2-5mm, moisture content ≤0.05%.

[0009] The nylon resin is a PA66 slice having reactive amino groups at the end thereof, the PA66 slice has a melting point of 255-265° C., a relative viscosity of 2.6±0.6, and a terminal amino group content of ≥90 mmol / kg.

[0010] The mass fraction of epoxysilicone in the sizing agent solution is 1%-10%, and the density of epoxysilicone is 1.050±0.06g / cm 3 , silicon content 16.9%, epoxy equivalent 206.3, epoxy value 0.48 / 100g, the general structure is as follows:

[0011]

[0012] The compatibilizer is epoxycyclohexyl-cage polysilsesquioxane with a density of 1.31±0.1 g / cm 3 , epoxy equivalent 177.2, epoxy value 0.56 / 100g, silicon content 15.8%, the general structure is as follows:

[0013]

[0014] The antioxidant is a compound of triphenyl ketone phosphate hexamer and potassium iodide, the ratio of triphenyl ketone phosphate hexamer to potassium iodide is 9:1-1:9, and the two form a coordination ion with reducing property.

[0015] The other additives may be one or more of a lubricant and a colorant.

[0016] The preparation method of the above-mentioned freezing liquid resistant nylon material used in the thermal management system of new energy vehicles comprises the following steps:

[0017] (1) Weigh various dried raw materials according to the formula ratio;

[0018] (2) Mix nylon resin, compatibilizer, antioxidant and other additives uniformly by high-speed mixer;

[0019] (3) Weighing the modified glass fiber according to the ratio;

[0020] (4) The resin and additive mixture is added through the main feed port of a twin-screw extruder, and the modified glass fiber is added from the side feed port of the twin-screw extruder. After melt extrusion, granulation, drying and other processes, the above-mentioned freezing liquid resistant nylon material is obtained.

[0021] The above-prepared freezing liquid resistant nylon material can be applied to automotive thermal management system PTC outer panels, thermostats, water valves and other components.

[0022] The advantage of the present invention is that the nylon material prepared by glass fiber pretreatment and formula design meets the requirements of automotive thermal management system parts for mechanical properties, freezing liquid resistance and long-term thermal oxidation aging performance. According to the structural characteristics of nylon materials and the freezing liquid resistance failure mechanism, the interface reaction between the modified glass fiber prepared by attaching epoxy siloxane to the surface of the glass fiber and the nylon resin increases the compatibility of the glass fiber and the resin. In the formula design, epoxy cyclohexyl-cage polysilsesquioxane is selected as a compatibilizer, and the terminal groups of the nylon resin are limited at the same time. The interfacial bonding force of nylon and glass fiber is increased by the joint action of "similar compatibility" and "chemical compatibilization". The "hydrophobic" effect brought by the silicon element in the compatibilizer further improves the freezing liquid resistance of the nylon material. In the formula design, the present invention selects triphenylphosphoketone hexamer and potassium iodide compound as functionalized auxiliary agents, and the two are compounded to form a reducing coordination ion. The coordinated ions have the lowest potential and higher reducing ability, can react with oxygen, free radicals, etc. preferentially, further protect the polymer from oxidative damage, and improve the performance retention rate of the nylon material in high-temperature freezing liquid. At the same time, the triphenylphosphoacetic acid hexamer has hydrophobicity and "steric hindrance" effect, and will not be extracted and become ineffective due to the freezing liquid environment. The nylon material prepared by the present invention has excellent mechanical properties, long-term thermal oxidation aging properties and freezing liquid resistance.

[0023] The beneficial effects of the present invention are:

[0024] 1) The present invention selects epoxysiloxane to attach to the surface of glass fiber, and the prepared glass fiber and nylon resin have better interface bonding strength and compatibility through the action of chemical bonds. The prepared nylon material has excellent freezing liquid resistance and mechanical properties.

[0025] 2) The formula design selected epoxy cyclohexyl-cage polysilsesquioxane as a compatibilizer, which increased the interfacial bonding strength of nylon and glass fiber through the combined effects of "similar compatibility" and "chemical compatibilization". The "hydrophobic" effect brought by the silicon element in the compatibilizer further improved the nylon material's resistance to freezing liquids.

[0026] 3) The nylon grease selected in the formula design of the present invention limits the type and content of the terminal groups according to the types of active groups of the glass fiber surface treatment agent and the compatibilizer, which is beneficial to the formation of chemical bonds between the nylon resin and the glass fiber interface through the reaction of active groups during the preparation of the freeze-resistant nylon material, thereby increasing the interfacial bonding force between nylon and glass fiber, thereby increasing the freeze-resistant performance of the nylon material.

[0027] 4) The present invention selects triphenylphosphoacetic acid hexamer and potassium iodide compound as functionalized auxiliary agents in the formula design, and the two are compounded to form a reducing coordination ion. The coordination ion has the lowest potential and higher reducing ability, can preferentially react with oxygen, free radicals, etc., further protects the polymer from oxidative damage, and improves the performance retention rate of the nylon material in high-temperature freezing liquid. At the same time, triphenylphosphoacetic acid hexamer has hydrophobicity and "steric hindrance" effect, and will not be extracted and invalidated due to the environment of the freezing liquid.

[0028] 5) The preparation method of the present invention is simple, and the prepared nylon material takes into account mechanical properties, long-term thermal oxidation aging properties and resistance to freezing liquids, and is suitable for automotive thermal management system components, providing a material solution for new energy vehicle thermal management system components.

[0029] The above-mentioned beneficial effects achieve the excellent mechanical properties, long-cycle thermal oxidation aging properties and resistance to freezing liquid of nylon materials. DETAILED DESCRIPTION

[0030] In order to make the technical problems, technical solutions and intentions to be solved by the present invention clearer, the present invention will be further described in detail below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0031] The embodiments and comparative examples of the present invention use the following materials, but are not limited to the following materials:

[0032] Nylon resin, commercially available

[0033] Nylon resin PA66, trade name EPR27, produced by Shenma Engineering Plastics Co., Ltd.;

[0034] Glass fiber, trade name ECS301HP-3, produced by Chongqing International Composite Materials Co., Ltd.;

[0035] Modified glass fiber, homemade;

[0036] Compatibilizer, epoxycyclohexyl-cage polysilsesquioxane, commercially available;

[0037] The antioxidant triphenylphosphine hexamer is commercially available;

[0038] Antioxidant potassium iodide, commercially available;

[0039] Antioxidant H3386, produced by BRUGGOLEN;

[0040] Antioxidant 1098, hindered phenol antioxidant, commercially available;

[0041] Antioxidant 168, phosphite antioxidant, commercially available;

[0042] Processing aid. Product name LYSI-100E, produced by Chengdu Silike Technology Co., Ltd.

[0043] Masterbatch, trade name PA6-2015, commercially available;

[0044] Preparation methods of Examples 1-5 and Comparative Examples 1-5:

[0045] Preparation method of freezing liquid resistant nylon material:

[0046] (1) Weigh various dried raw materials according to the formula ratio; mix nylon resin, compatibilizer, antioxidant and other additives by high-speed mixer and set aside; weigh modified glass fiber according to the ratio and set aside.

[0047] (2) The resin and additive mixture is added through the main feed port of a twin-screw extruder, and the modified glass fiber is added from the side feed port of the twin-screw extruder. After melt extrusion, granulation, drying and other processes, the above-mentioned freezing liquid resistant nylon material is obtained.

[0048] Preparation of test specimens of nylon material resistant to freezing liquid:

[0049] The above materials were dried in a forced air drying oven at 120° C. for 4 hours and then injection molded into standard specimens at an injection molding temperature of 280-330° C. The prepared mechanical properties specimens were conditioned in a standard laboratory environment (23° C., 50% RH) for 24 hours before testing.

[0050] Test methods for each performance index:

[0051] Tensile properties: According to ISO 527 method, sample size: 170*10*4mm, test speed 5mm / min.

[0052] Bending properties: According to ISO 178 method, sample size: 80*10*4mm, test speed 2mm / min.

[0053] Notched impact performance: According to ISO 179 method, sample size: 80*10*4mm.

[0054] Heat deformation temperature: according to ISO 75 method, sample size: 80*10*4, test condition: 1.8MPa.

[0055] Tensile strength retention rate (thermal oxidation aging): 1) After the injection molded specimens are conditioned in a laboratory environment, the tensile strength tested according to ISO 527 is recorded as the tensile strength before aging; 2) After the standard test specimens are placed in a 180°C oven for 3000 hours, the tensile strength is tested according to the ISO 527 method after conditioning for 24 hours in a laboratory environment (23°C, 50% RH) and recorded as the tensile strength after aging-A; 3) Tensile strength retention rate-A = tensile strength before aging / tensile strength after aging-A*100%.

[0056] Tensile strength (resistance to freezing liquid): Place the standard test specimen in a 130°C, 50% ethylene glycol solution for 1008 hours, then take it out and cool it to room temperature. After conditioning it in a laboratory environment (23°C, 50% RH) for 12 hours, test the tensile strength according to ISO 527 method.

[0057] Table 1: Composition and properties of nylon materials in Examples 1-5 and Comparative Examples 1-5

[0058]

[0059]

[0060] It can be seen from the results of the embodiments and comparative examples in Table 1 that the terminal amino content of nylon resin, glass fiber pretreatment, compatibilizer and antioxidant in the formula are key factors affecting the freezing liquid resistance and long-term thermal oxidative aging performance of nylon materials. It can be seen from Examples 3-5 and Comparative Example 1 that the introduction of epoxy cyclohexyl-cage polysilsesquioxane in the formula design can improve the mechanical properties, freezing liquid resistance and thermal oxidative aging performance of nylon materials. It can be seen from Example 3 and Comparative Examples 1 and 4 that epoxy siloxane has a positive effect on the improvement of the freezing liquid resistance of nylon materials by pretreatment of glass fiber surface. This is because epoxy siloxane increases the interfacial bonding force of nylon and glass fiber through the combined effects of "similar compatibility" and "chemical compatibilization", and the "hydrophobic" effect of silicon in epoxy siloxane further improves the freezing liquid resistance of nylon materials. It can be seen from Example 3 and Comparative Example 5 that the high-end amino group of nylon resin can improve the thermal oxidation aging performance and freezing liquid resistance of nylon material, because the end amino group reacts with the glass fiber surface and the maleic anhydride group of the compatibilizer to increase the interfacial bonding force between nylon resin and the glass fiber surface. It can be seen from Examples 1-3 and Comparative Examples 2-3 that the antioxidant system used in the present invention is better than organic copper salts, hindered phenols and phosphite systems for freezing liquid resistance and long-term heat resistance, because the antioxidant system of the present invention has strong reducibility, and organic copper and organic halides can avoid the risk of antioxidant failure caused by freezing liquid extraction of metal ions in freezing liquid resistance, thereby improving the freezing liquid resistance of nylon material. Compared with traditional antioxidants, the heat resistance and freezing liquid resistance of nylon material are greatly improved. The nylon material prepared by the present invention has excellent freezing liquid resistance, long-term heat resistance and mechanical properties, and can be used for parts such as PTC outer panels, thermostats, and water valves of automotive thermal management systems.

Claims

1. A nylon material resistant to freezing liquid used in the thermal management system of new energy vehicles, characterized in that: The following raw materials are calculated by weight percentage: Composition: Nylon resin: 37-89.98%; Modified glass fiber: 10-55%; Compatibilizer: 0.01-5%; Antioxidant: 0.01-1%; The surface of the glass fiber is sizing treated with epoxysiloxane solution, and the mass fraction of the sizing agent is greater than 0.3%.

2. According to claim 1, a nylon material resistant to freezing liquid used in a thermal management system of a new energy vehicle is characterized by: The nylon resin is a PA66 slice with reactive amino groups at the end, the PA66 slice has a melting point of 255-265°C, a relative viscosity of 2.6±0.6, and a terminal amino content of ≥ 90mmol / kg.

3. The freezing liquid resistant nylon material used in the thermal management system of new energy vehicles according to claim 1, characterized in that: The modified glass fiber has an alkali content of less than 0.8% and a volume density of 0.6-0.8 g / cm 3 , single fiber diameter: 7-13μm, short cut length: 2-5mm, moisture content ≤0.05%.

4. The freezing liquid resistant nylon material used in the thermal management system of new energy vehicles according to claim 1, characterized in that: The mass fraction of epoxysilicone in the sizing agent solution is 1%-10%, and the density of epoxysilicone is 1.050±0.06g / cm 3 , silicon content 16.9%, epoxy equivalent 206.3, epoxy value 0.48 / 100g, the general structure is as follows:

5. The freezing liquid resistant nylon material used in the thermal management system of new energy vehicles according to claim 1, characterized in that: The compatibilizer is epoxycyclohexyl-cage polysilsesquioxane with a density of 1.31±0.1 g / cm 3 , epoxy equivalent 177.2, epoxy value 0.56 / 100g, silicon content 15.8%, the general structure is as follows:

6. The freezing liquid resistant nylon material used in the thermal management system of new energy vehicles according to claim 1, characterized in that: The antioxidant is a compound of triphenyl ketone phosphate hexamer and potassium iodide, the ratio of triphenyl ketone phosphate hexamer to potassium iodide is 9:1-1:9, and the two form a coordination ion with reducing property.

7. The freezing liquid resistant nylon material used in the thermal management system of new energy vehicles according to claim 1, characterized in that: The other additives are lubricants, colorants or a combination of several thereof.

8. The method for preparing the freezing liquid resistant nylon material used in the thermal management system of new energy vehicles according to any one of claims 1 to 7, characterized in that: The following steps are involved: Weigh various dried raw materials according to the formula ratio; Mix nylon resin, compatibilizer, antioxidant and other additives evenly with a high-speed mixer; Weigh the modified glass fiber according to the ratio; The resin and additive mixed raw material is added through the main feeding port of the twin-screw extruder, and the modified glass fiber is added from the side feeding port of the twin-screw extruder. After the processes of melt extrusion, granulation, drying and the like, the freezing liquid resistant nylon material is obtained.

9. The freezing liquid resistant nylon material used in the thermal management system of new energy vehicles according to any one of claims 1 to 7, characterized in that: This refrigerant-resistant nylon material is used in automotive thermal management system PTC outer panels, thermostats, water valve-related components.

Citation Information

Patent Citations

  • A resistant alcoholysis reinforced PA6T material and its preparation method

    CN112592583B

  • Hydrolysis-resistant alcoholysis-resistant reinforced nylon material and preparation method thereof

    CN115710429A

  • Low-carbon recyclable nylon pipeline for thermal management system

    CN221476399U

  • Environment-protective halogen-free glass fiber reinforced polyamide flame retardant

    CN107629450A

  • Water-based self-extinction polyurethane dispersion, and preparation method and composition thereof

    CN111944111A

Cited By

  • Laser etching clear refrigerating fluid-resistant nylon material and preparation method thereof

    CN121825229A